Aprovechamiento de los desechos orgánicos sólidos generados por los restaurantes ubicados en Chapinero, Bogotá, Colombia. Mediante el método de vermicompostaje. (2020)
When evaluating the accumulation and increase of solid organic waste throughout the Bogotá area, it is necessary to seek the application of technologies that are sustainable and friendly to the environment. Due to the growing interest worldwide to recycle and also to reduce pollution and internalize the principles of the circular economy. One of the most effective methods is vermicomposting. In fact, the Superintendency of Public and Home Services (Superservices) estimates that between 60% and 70% of the solid waste generated can be used in this way. In addition, this practice is useful because it is estimated that 50% of the daily trash thrown into the landfill is decomposing organic matter. The emergence of this project aims to make a good quality humus and thus take advantage of solid organic waste in one of the sectors that generates this type of organic solid waste, which is the commercial sector of restaurants located in the town of Chapinero in Bogotá, Colombia. where a problem is the daily generation of waste from the nearly 523 establishments that are located in a small area. The project consists of different stages for its realization: sampling of the raw material taken from the sector, collection and transport of waste, conditioning of waste in order to adjust the fundamental parameters for the vermicomposting process. The process that is generated is semi-continuous in which organic matter is added approximately every 15 days and the fundamental parameters are controlled with a vermicomposter. This process is finished in a time of 90 days, when observing that the humus already has the final physical characteristics. Soil and water analyzes are carried out with the final product.